Kepemilikan Asing Memoderasi Pengaruh Kualitas Laporan Keuangan dan Efisiensi Investasi - Meitari, I Gusti Ayu Ary; Astika, Ida Bagus Putra (E-Jurnal Akuntansi; Vol 31 No 8 (2021), 2021)
Mining company is part of the industrial sector, need large capital and also work on long-term projects. Mining company need to use their capital efficiently so that company can obtain maximum income from operational activities. To realize that, mining company need to concern on factors that affect investment efficiency. The purpose of this study examines the influence of the quality of financial reporting and foreign ownership on investment efficiency. The sample was obtained by purposive sampling method from 42 mining companies listed on the Indonesia Stock Exchange (IDX) and found 45 samples of observation from 2014-2016. Based on the analysis using simple linear regression and moderate regression analysis shows that the quality of financial reporting has a positive effect on investment efficiency and foreign ownership has a role to strengthen the influence of the quality of financial reporting on investment efficiency. Keywords: Investment Efficiency; The Quality Of Financial Reporting; Foreign Ownership.